Information technology governance, funding and structure - Ismail, Noor Azizi (Emerald Group Publishing Limited, 2008)
Purpose - The paper's purpose is to investigate the issues of IT governance, funding and structure of a public university in Malaysia.Design/methodology approach- The study uses a case study approach, i.e. a series of interviews with users and information services provider of a campus information system.Findings - The university lacks a common approach to decision making or fonim for making comprehensive assessments of IT planning and funding strategy. The campus information system was developed in an uncoordinated manner, reflecting interests of different departmental units, and a decision support system is almost non-existent. A new IT planning structure with clear roles and responsibilities is proposed to overcome existing barriers to effective campus information system. Originality/value - This is the first study to investigate the issue of IT governance, funding and structure in Malaysian universities using a case study approach. Paper type- case study.